Compliance and Related Outcomes of Prophylactic Antibiotics in Traumatic Open Fractures. (June 2020) - Johnson, Hannah C.; Bailey, Abby M.; Baum, Regan A.; Justice, Stephanie B.; Weant, Kyle A.
Purpose: Prophylactic antibiotic therapy is a standard of care for patients who present with open fractures due to the risk of infectious complications. This study was conducted to characterize the use of initial prophylactic antibiotic use in open fractures, guideline compliance, and its impact on care.Methods: Retrospective chart review of adult patients presenting with an open fracture to a Level 1 Trauma Center Emergency Department over a 12-month period was conducted.Results: Of the 202 patients meeting inclusion criteria, overall compliance with guideline recommendations for antibiotic prophylaxis was found to be 33.2%. The duration of prophylactic therapy was significantly longer in the noncompliant group and among those who received a secondary antibiotic ( P < .05 for both comparisons). The duration of therapy was found to be significantly longer in those patients who developed an infection ( P < .001). Those who developed an infection had a longer hospital length of stay (LOS) ( P < .001) and intensive care unit LOS ( P = .002). In addition, those who developed an infection had significantly more surgeries ( P < .001) and received more red blood cell transfusions ( P < .001). Correlation analysis confirmed a significant association between infection and duration of antibiotic prophylaxis ( P = .02), number of surgeries ( P < .0001), and number of transfusions ( P < .0001).Conclusion: Guideline compliance was exceedingly low due to the extended duration of initial antibiotic therapy and did not appear to yield any clinical benefits. Infection was significantly associated with longer duration of initial prophylactic therapy and morbidity. Opportunities exist to elevate compliance with guidelines and to reevaluate prophylactic antimicrobial therapy in this setting.